2014
DOI: 10.1002/ppap.201300174
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Serum Derived Proteins with Sub‐Micrometer Structured Surfaces

Abstract: This work presents the development and optimization of two fabrication methods that combine plasma polymerization and electron beam lithography techniques for producing chemical patterns at the sub-micro scale. The first method uses sacrificial resist as mask to produce the functionalization of the bioadhesive areas and the second method consists in the direct EBL writing of adhesive regions on a non-adhesive plasma deposited PEO-like film. The produced patterned surfaces exhibit high binding capacity as teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…It is clear that the e-beam treatment prevents the adsorption of the Au NPs on the PEOlike coatings, the surface coverage decreases from 13.3% on the as-deposited area to 1.8% for the 12 pC mm À2 e-beam irradiated sample and to 0.09% for the 85 pC mm À2 e-beam irradiated sample. Our previous work 17 showed that the main effect of the e-beam treatment on PEO-like coatings is the increase in refractive index of the lm, which indicates an increase of the crosslinking between the polymeric chains.…”
Section: Immobilization Of Au Nps On Peo-like Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the e-beam treatment prevents the adsorption of the Au NPs on the PEOlike coatings, the surface coverage decreases from 13.3% on the as-deposited area to 1.8% for the 12 pC mm À2 e-beam irradiated sample and to 0.09% for the 85 pC mm À2 e-beam irradiated sample. Our previous work 17 showed that the main effect of the e-beam treatment on PEO-like coatings is the increase in refractive index of the lm, which indicates an increase of the crosslinking between the polymeric chains.…”
Section: Immobilization Of Au Nps On Peo-like Coatingsmentioning
confidence: 99%
“…Synthesis of 15 nm sized Au NPs was carried out by modication of the procedure described by Turkevich et al, 17 in which the gold nanoparticles are produced by the reduction of the gold salt by the sodium citrate that acts as a reducing agent and stabilizer. In this work, the solution was heated up using a specialized microwave apparatus (Discover S by CEM corporation) to ensure a highly reproducible rapid heating.…”
Section: Gold Nanoparticles Synthesismentioning
confidence: 99%
“…2,2-Bis(5-methylhexyl)propanediol (3b). Yield 95%; colourless liquid; d H (200 MHz, CDCl 3 , ppm): 3.57 (s, 4H), 2.00 (s, 2H), 1.51 (m, 2H), 1.22 (m, 16H), 0.85 (d, 3 J HH ¼ 6.6 Hz, 12H).…”
Section: Monomer Synthesis and Characterizationmentioning
confidence: 99%
“…Various hydrophobic substituents can be graed on the monomers to modify the intrinsic polymer hydrophobicity. For the growth of nanobers, polyaniline, 26,27 polypyrrole, [28][29][30] poly (3,4-ethylenedioxythiophene) (PEDOT) [31][32][33][34][35] or poly (3,4-propylenedioxythiophene) (PProDOT) [36][37][38] derivatives have been described in the literature. One of the advantages of using ProDOT derivatives is the various possible positions for controlled substitution by hydrophobic substituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation